Protein potential of cricket (Acheta domesticus) flour as a sustainable alternative for human consumption - Morillo Cruz, Cesar Gerardo (2024)
The global population growth, the increase in protein demand and the reduction of agricultural land, the sustainable production of meat is a challenge for the next decades. Therefore, this research seeks to develop cricket (Acheta domesticus) flour as an alternative for human consumption by evaluating its protein capacity, making entomophagy the food of the future. The crickets were collected from January to April because of their abundance due to the constant rains, bred in captivity and slaughtered in their adult state for the production of flour. FAO points out that insects offer high quality proteins and nutrients, surpassing meat and fish in quality. The results indicated that cricket meal has a protein value of 67.66%, ash 4.73%, fiber 11.60%, fat 1.17% and carbohydrates 14.84%, in comparison with other protein sources of either animal or vegetable origin, shows a wide superiority. Regarding microbiological quality, the flour reports “absence” of Salmonella sp., Escherichia coli, yeasts and molds. The microscopic results of helminthic and entomological load were “absence”, concluding that the innovative insect flour product has a high protein content and acceptable microbiological quality.